Cloning and sequence analysis of Paralichthys olivaceus Follistatin cDNA - LIU Qing-hua; TAN Xun-gang; XU Yong-li; ZHANG Pei-jun; XU Peng (浙江大学学报. 农业与生命科学版)
To study the DNA sequence features of Follistatin gene in marine fish, Paralichthys olivaceus Follistatin cDNA was isolated and analyzed from Paralichthys olivaceus embryos 67 h after fertilization. The results indicated that there was no evidence for alternative splicing of Follistain in Paralichthys olivaceus. The length of Paralichthys olivaceus Follistatin cDNA was 963 bp. Sequence analysis revealed that Paralichthys olivaceus Follistatin was more closely related to Takifugu rubripes. The biological function of the highly conserved cysteine and glycin in Paralichthys olivaceus Follistatin protein might be maintaining the stabilization of protein structure.